AAP, Apps and WhatsApp - Stéphanie Tawa Lama (South Asia Multidisciplinary Academic Journal)
The Aam Aadmi Party (AAP), a young party that has been governing the city-state of Delhi since 2015, has placed (i) the fight against corruption; (ii) the development of participatory democracy; and (iii) good governance at the center of its agenda. The official discourse of the party, in its formative years, promoted participation through a major promise: if voted to power, it would govern with the people. This paper investigates the meanings and forms taken by this promise over the years. On the basis of (i) a textual analysis of the party’s “political text and talk” (manifestoes, speeches, interviews) and (ii) the observation of various participatory practices that it implemented over the years, the paper examines the AAP’s changing approach to participation. It focuses on the evolving technological infrastructures of these participatory experiments and shows that even as the dominant definition of participation evolved from “discussion” to “surveillance,” increasing reliance on high-tech, digital tools has meant that citizen participation, which was initially essential to its program, has become in the end nothing more than a means of political communication.